2018
DOI: 10.1021/acs.est.8b02648
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry Illuminates Ubiquitous Organic Matter Fluorescence Spectra

Abstract: Dissolved organic matter (DOM) in aquatic environments forms a vast reservoir of carbon present as a complex supermixture of compounds. An efficient approach to tracking the production and removal of specific DOM fractions is needed across disciplines, for purposes that range from improving global carbon budgets to optimizing water treatment in engineered systems. Although widely used to study DOM, fluorescence spectroscopy has yet to deliver specific fractions with known spectral properties and predictable di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(102 citation statements)
references
References 41 publications
11
88
0
Order By: Relevance
“…Therefore, the distribution of the chemical composition of the samples used in this study is consistent with selectivity of the conventional (alkaline) extraction methods for similar redox active moieties. Similar conclusions have been drawn from other types of evidence, such as near edge X-ray absorption ne structure (NEXAFS) spectra, 158 collision induced dissociation coupled to FTICR MS, 159 solid phase extractions and FTICR MS, 22 uorescence spectroscopy coupled to PARAFAC analysis, 160 and statistical analysis of chemical composition data for hundreds of NOMs. 21,29 A few of the NOMs from this study distribute along a diagonal in Fig.…”
Section: Relationship To Chemical Compositionsupporting
confidence: 72%
“…Therefore, the distribution of the chemical composition of the samples used in this study is consistent with selectivity of the conventional (alkaline) extraction methods for similar redox active moieties. Similar conclusions have been drawn from other types of evidence, such as near edge X-ray absorption ne structure (NEXAFS) spectra, 158 collision induced dissociation coupled to FTICR MS, 159 solid phase extractions and FTICR MS, 22 uorescence spectroscopy coupled to PARAFAC analysis, 160 and statistical analysis of chemical composition data for hundreds of NOMs. 21,29 A few of the NOMs from this study distribute along a diagonal in Fig.…”
Section: Relationship To Chemical Compositionsupporting
confidence: 72%
“…Note that all the validated models appear to capture a bit of the Rayleigh and Raman scattering despite our effort to completely remove it from the data set. After many attempts, it was found that we were losing the protein‐like signal if we tried to remove too much of the scattering (i.e., by enlarging the widths of the scattering band to be removed), similar to what has been alluded by Bro (1997) and Murphy et al (2018). This problem, due largely to the relatively high noise in our data set built primarily on blue water samples with low fluorescence intensities, at least partly explains the small emission elevations over 540–600 nm in C2 and C4 (Figure 2).…”
Section: Resultsmentioning
confidence: 76%
“…In particular, four of our components (C1–C4) were also identified by Jørgensen et al (2011) in marine water samples collected from both coastal regions and open oceans. Based on the results of previous studies (e.g., Chen et al, 2003; Coble, 1996; Jørgensen et al, 2011; Murphy et al, 2018), C2 and C3 are designated as humic‐like FDOM, and C1, C4, and C5 as protein‐like FDOM. Note that all the validated models appear to capture a bit of the Rayleigh and Raman scattering despite our effort to completely remove it from the data set.…”
Section: Resultsmentioning
confidence: 99%
“…Absorption and emission spectra from the optically active fraction of DOM relate to DOM biochemistry, and are widely used to estimate DOM composition (Stedmon et al, 2003;Hernes et al, 2009;Fellman et al, 2010a). Analyzing EEMs to discern biochemical characteristics carries distinct advantages: measurements are inexpensive, rapid, and sensitive, with capacity for large throughput.…”
Section: Optical Parameters and Seasonal Change In Optically Active Cmentioning
confidence: 99%